1991
DOI: 10.1007/bf00012499
|View full text |Cite
|
Sign up to set email alerts
|

A framework to correlate a/W ratio effects on elastic-plastic fracture toughness (J c )

Abstract: Single edge-notched bend (SENB) specimens containing shallow cracks (a/W < 0.2) are commonly employed for fracture testing of ferritic materials in the lower-transition region where extensive plasticity (but no significant ductile crack growth) precedes unstable fracture. Critical J-values (J,.) for shallow crack specimens are significantly larger (factor of 2-3) than the J,-values for corresponding deep crack specimens at identical temperatures. The increase of fracture toughness arises from the loss of const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
9

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(103 citation statements)
references
References 24 publications
4
90
0
9
Order By: Relevance
“…Thus, the biaxiality ratio or the Tstress corresponds to the observed experimental trends, and is a qualitative index of the relative crack-tip constraint levels for various geometries with a positive value representing a high level of constraint and a negative value denoting a low level of constraint. The elastic-plastic FEA results of Dodds et al [253] have shown that for any two cracks having the same K (or J) at their crack tips the crack-tip stress and strain fields can be different if the constraint levels are different. Bilby et al [254] showed that the T-stress can dramatically affect the magnitude of hydrostatic triaxiality in the immediate vicinity of the crack tip.…”
Section: The J-t Approachmentioning
confidence: 99%
“…Thus, the biaxiality ratio or the Tstress corresponds to the observed experimental trends, and is a qualitative index of the relative crack-tip constraint levels for various geometries with a positive value representing a high level of constraint and a negative value denoting a low level of constraint. The elastic-plastic FEA results of Dodds et al [253] have shown that for any two cracks having the same K (or J) at their crack tips the crack-tip stress and strain fields can be different if the constraint levels are different. Bilby et al [254] showed that the T-stress can dramatically affect the magnitude of hydrostatic triaxiality in the immediate vicinity of the crack tip.…”
Section: The J-t Approachmentioning
confidence: 99%
“…fail by transgranular cleavage [10]. This more detailed study would require meshes with 2-3 times the number of nodes and elements.…”
Section: Reference J Solutions For Semi-elliptical Surface Cracks In mentioning
confidence: 99%
“…This is called the constraint effect. Many studies have been conducted on the effect of the constraint (4), (5) . Practically, the local approach method (6), (7) gave one solution to the constraint condition problem.…”
Section: Introductionmentioning
confidence: 99%